Tratamiento Informativo sobre el COVID 19 en la Plataforma Digital del Universo, marzo - agosto 2020. - Paguay Tenempaguay, Marco Antonio (2022)
This research called "Informational treatment on Covid-19 on the digital platform El Universo, March-August 2020" was developed to know the handling given to the informational content on Covid-19, on the platform newspaper of the newspaper El Universo. The same one is guided by the functionalist theory, which deals with communication as a connection between the medium and the reader, in addition, that it focuses on social behavior. Therefore, the project is based on knowing the point of view of El Universo newspaper's relationship with the new pandemic. The following research methods used are: scientific, qualitative, analytical, and bibliographic-documentary; As it is qualitative, it does not require a population and a sample. Also, an analysis was made of the journalistic notes published on the digital platform. Interviews were also carried out with journalists and editors of the newspaper El Universo to learn more about the treatment they have given it. To the content of COVID-19. And based on the analysis of journalistic notes and interviews, a Communication Strategies Manual was proposed to improve the information management of the pandemic in the media with a digital platform.